2008
DOI: 10.1111/j.1742-4658.2008.06635.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of the biofilm‐related and carnosine‐hydrolyzing aminoacylhistidine dipeptidase from Vibrio alginolyticus

Abstract: Vibrio alginolyticus is one of twelve recognized marine Vibrio species that have been identified as pathogenic for humans and marine animals. This species causes infection in shrimps, fish, shellfish and squids, as well as in humans who are infected via consumption of undercooked seafood or exposure of wounds to warm seawater in coastal areas [1][2][3]. V. alginolyticus infects grouper culture by forming a biofilm in the intestine and causes fish mortality due to gastroenteritis syndrome [4]. A disease outbrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Biochemical studies of V. alginolyticus PepD revealed its metal-dependent characteristics (36) and optimal activation of Secondary structure elements are shown in red for ␣-helices and blue for ␤-strands. Gray spheres represent the zinc ions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Biochemical studies of V. alginolyticus PepD revealed its metal-dependent characteristics (36) and optimal activation of Secondary structure elements are shown in red for ␣-helices and blue for ␤-strands. Gray spheres represent the zinc ions.…”
Section: Resultsmentioning
confidence: 99%
“…apo-PepD has been observed with various divalent metal ions, including Mn 2ϩ , Co 2ϩ , Ni 2ϩ , Cu 2ϩ , and Cd 2ϩ (36). Previous studies have shown that the addition of Co 2ϩ ions to apo-PepD increases the enzymatic activity by a factor of ϳ1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations